The Serbian question in the allied policy towards Yugoslavia in 1944 - Zorić Mirjana (Војно дело, 2015)
Politico-military outcome in Yugoslavia, which followed after the operations of the People's Liberation Army of Yugoslavia and units of the Red Army during the liberation of Serbia in the autumn of 1944, dispelled many expectations that, once the occupying forces had departed, it would become the site of a bloody civil war between the Partisans and the Chetniks, with unforeseeable consequences. Civil war was averted owing to the entrance of the Red Army and combat support that the Red Army provided to the People's Liberation Army of Yugoslavia in Serbia. By their political support to Tito and his forces since mid-1944, the Western Allies, especially the British, decisively contributed to 'picking the winners' in the Yugoslav war outcome, enabling the communists to end the war as the absolute winners. On the other hand, without the support and assistance of the Allies, the Yugoslav Army in the Fatherland and its leader remained abandoned against the winds of political events that suited their greatest internal enemy: at the end of the war, Serbia found itself in the 'grip' of communists and the movement led by them. The politico-military outcome in Serbia in 1944 affected also the fate of Yugoslavia after the war. Sources of domestic and foreign origin, as well as modern historiographical literature, provide arguments that the great powers in the war - Germany, on the one side, and the USSR, the United Kingdom and the United States, on the other, figured that also the Yugoslavian question depended on resolving the Serbian question. Who will 'possess' Serbia in certain stages of the war and after its completion was important not only in terms of the internal relations (Chetniks-Partisans), but also in the context of the relations between allies (especially Soviet-British relations) during World War II. Due to its geopolitical position and economic importance, Serbia was equally an object of direct and global interests of the occupying forces, allies and other actors in Yugoslav theater of war, who proceeded from different positions and sought a definite resolution, the outcome of which remained uncertain for all parties almost to the end of the war.